An optimization problem for some nonlinear elliptic equation - Mohsen Zivari-Rezapour (Kuwait Journal of Science)
In this paper we prove existence and uniqueness of the optimal solution for anoptimization problem related to a nonlinear elliptic equation. We use the concepttangent cones to derive the optimality condition satisfied by optimal solution.